PENGARUH TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, SKALA USAHA DAN LAMA USAHA TERHADAP KUALITAS LAPORAN KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH - Indriyani, Tiyas (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: This research aims to analyze the influence of education level, understanding of accounting, business scale and length of business on the quality of financial reports in MSMEs in Imogiri District. The research uses a quantitative approach. The population of this research is MSMEs in Imogiri District which are registered in the Information System of the Department of Trade, Cooperatives, SMEs and Industry (SIDAKUI) Bantul Regency for the 2021 period with a sample of 88 MSMEs selected using the purposive sampling method. The data analysis technique used is multiple linear regression analysis with the help of the SPSS 25.0 for Windows application. The results of the research show that the level of education, scale of business and length of business have no effect on the quality of financial reports, while understanding accounting has a significant positive effect on the quality of financial reports. Keywords: Education Level, Understanding of Accounting, Business Scale, Length of Business, Quality of Financial Reports, MSMEs.